Assessment of Agronomic Effectiveness of Phosphate Rocks Applied to an Ultisol - Hashim, Zulkifli (1996)
Phosphate rocks (PR) available in Malaysia market are originated from North Carolina (NCPR), Gafsa, Tunisia (GPR), China (CPR), Jordan (JPR), Morocco (MPR) and Christmas Island (CIPR). Little information is available on their fate when applied to Malaysian soils in terms of their dissolution and agronomic effectiveness. Thus, a laboratory and glasshouse experiments to evaluate the extent of agronomic effectiveness during one year after PR application to a Rengam series soil were carried out. The objectives of the study were: (1) to characterize the chemical and some mineralogical properties of these PR and evaluating their solubity and dissolution with time. (2) to characterize the immediate and residual availability of P in the different fractions or compartments during one year after PR application using a laboratory exchange kinetic experiment (E Value). (3) to determine the plant P uptake and the relative agronomic effectiveness (RAE) of these PR using isotopic dilution techniques (L Value )on oil palm seedling grown for 12 months in the glasshpouse. The indirect solubility tests assessed by 2% fonnic acid (FA), 2% citric acid (CA) and neutral ammonium citrate (NAC) gave positive correlation with P uptake by oil palm seedling in the glasshouse. Neutral ammonium citrate (NAC) proved a better indicator of PR solubility and its correlation coefficient with P uptake improved by expressing citrate solubility as percent of rock rather than as percent of total P 205' The direct method to detennine the PR dissolution in the soil planted with oil palm seedlings for one year after PR application in the glasshouse was assessed by determining the dissolved inorganic P (Pi) by O.SM NaOH, Pi strip and labile P (isotopic dilution technique) and dissolved Ca by 1M NH40Ac. The results varied quite greatly among PRo The more reactive PR (more soluble as determined with FA, CA and NAC) such as North Carolina (NCPR) and Gafsa (GPR), dissolved more than those from Christmas Island (CIPR) and China (CPR). All the direct methods tested gave high correlation with plant P uptake throughout the one year growing period, with O.5M NaOH being the best direct method for determining PR dissolution in the soil planted with oil palm seedling.